Targeted amplification-based whole genome sequencing of Monkeypox virus in clinical specimens - S. Isabel; A. Eshaghi; V. R. Duvvuri; J. B. Gubbay; K. Cronin; Aimin Li; M. Hasso; S. T. Clark; J. P. Hopkins; S. N. Patel; T. W. A. Braukmann (Microbiology Spectrum, 2024)
ABSTRACT The 2022 mpox outbreak has led to more than 91,000 cases in 115 countries. Whole genome sequencing (WGS) has been at the forefront of surveillance and outbreak investigations for different pathogens of public health significance. Many institutions performing WGS on Monkeypox virus (MPXV) use a resource-intensive metagenomic approach. Here we present a targeted amplification method for WGS of MPXV from clinical specimens. We designed 43 pairs of primers (amplicons ~5 kb) with PrimalScheme to span the ~200 kb viral genome and then added 12 additional primers to optimize amplification. We extracted nucleic acid from clinical specimens and amplified the two primer pools. All libraries were sequenced on the MiniSeq platform. Resulting reads were filtered by quality and then mapped to a MPXV reference genome. Consensus sequences were generated for phylogenetic analysis. A total of 91 specimens with a real-time-PCR cycle threshold (Ct) values ≤27.9 were sequenced using our targeted amplification protocol. The sequenced MPXV genomes were of high quality with mean genome coverage of 99.56% (95% CI 99.32-99.80%), mean depth 1,395× (95% CI 1275–1515), and mean mapping quality of 52.87 (95% CI 52.1–53.6) and allowed for greater multiplexing of samples relative to metagenomics. The MPXV genomes belong to 8 of the 13 clades observed during the 2022 global mpox outbreak. Targeted amplification enrichment provides high coverage, throughput, and short turnaround times. It is an efficient low-cost method for MPXV WGS and can benefit public health surveillance and outbreak management. IMPORTANCE We present a protocol to efficiently sequence genomes of the MPXV-causing mpox. This enables researchers and public health agencies to acquire high-quality genomic data using a rapid and cost-effective approach. Genomic data can be used to conduct surveillance and investigate mpox outbreaks. We present 91 mpox genomes that show the diversity of the 2022 mpox outbreak in Ontario, Canada.